Agua, fator limitante ao desenvolvimento : a regiäo de Maringá - Paraná - Lopes, José Carlos de Jesus (2001)
The present dissertation has been developed in order to analyse the water as a limited factor on development in Maringá, city located in Paraná North State, Brazil. Define the water scarcity concept and the new sustainable development paradigm to the water resources and the water resources planning and management on the river basin. Verify the factors that contaminate and degrade the water resources in Pirapó river basin. Also exam the relationship between urban concentration, urban, industrial and farmers spills those are threw away on Pirapó river basin?s water